1992
DOI: 10.1111/j.1467-9280.1992.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Bias for Forward-Facing Motion

Abstract: When an occlitded horizontal row of shapes is shifred laterally, apparenr motion can be experienced in either the lefrward or the rightward direction. Foitr experiments provide evidence for a motion bias in the direction that shapes appear to face. The bias tended to be largest when directionality was specified geometrically (e.g.. triangles), next largest when it was specified biologically (e.g., mice). and absent when it was speciBed calligraphically (e.g., letter R). The bias increased parametrically as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 20 publications
(12 reference statements)
3
54
0
Order By: Relevance
“…Halpern and Kelly (1993) did not find a typicalvelocity effect. In the apparent motion study, a typicaldirection effect was found, but its influence was weaker than the pointedness effect (McBeath et al, 1992). These findings might imply that knowledge about object-specific motions has a weaker influence on RM than does the pointedness of objects.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Halpern and Kelly (1993) did not find a typicalvelocity effect. In the apparent motion study, a typicaldirection effect was found, but its influence was weaker than the pointedness effect (McBeath et al, 1992). These findings might imply that knowledge about object-specific motions has a weaker influence on RM than does the pointedness of objects.…”
Section: Discussionmentioning
confidence: 69%
“…A pointedness effect was also found in an apparent motion study (McBeath, Morikawa, & Kaiser, 1992) and in a study of memory distortion by static stimuli (Freyd & Pantzer, 1995). These findings suggested that the pointedness of objects influences the perceptual system and, hence, RM.…”
Section: Discussionmentioning
confidence: 84%
“…When an object was misaligned with its trajectory by 15 degrees to the right, for example, the judgment was biased by about 10 degrees to the right from the true trajectory. Other research has similarly demonstrated that direction judgments can be biased by orientation (Freyd & Finke, 1984;McBeath, Morikawa, & Kaiser, 1992;Palmer, 1980;Werkhoven, Snippe, & Koenderink, 1990;). Freyd (1983) demonstrated that just the structure of an object can imply motion that makes people perceive the last position of a moving object to be displaced in the direction implied by the orientation.…”
mentioning
confidence: 99%
“…Analysing the reasons for that are not easy given the present data, but one possibility is that most individuals, regardless of handedness, tend to scan from left to right (see, for instance, Ebersbach et al, 1996, who suggest that initial visual exploration usually begins on the left). That may of course be secondary in part to reading direction (Chokron, Bartolomeo, Perenin, Helft, & Imbert, 1998;Dobel, Diesendruck, & Bö lte, 2007;Fagard & Dahmen, 2003), or perhaps to a bias in perception of forward-facing motion (which has been suggested to relate to perception of the duckÁrabbit figure; see McBeath, Morikawa, & Kaiser, 1992), but even so, as one referee pointed out to us, it should still mean that the more duck-like Wittgenstein figure should be seen more as a rabbit when laterally reversed, as in Figure 3. To our eye it does not, primarily looking like a duck either way, but that would benefit from formal testing.…”
Section: Discussionmentioning
confidence: 99%